The Historical Change of the Perception of Greater Colonial Seoul (1920-1935) - Kim, Youngjoon; Nakajima, Naoto (International Planning History Society Proceedings, 2024)
A century ago, Colonial Seoul's (Keijo in Japanese) population surpassed 250,000, resulting in rapid urbanization exceeding 5,000 people per square kilometers. This led to challenges related to housing, hygiene, and traffic congestion. This study examines how Colonial Seoul residents' perception of the city's extent changed in the 1920s-30s and how authorities responded through urban planning based on newspaper articles and official urban planning documents. Through this investigation, the following implications can be derived: First, just a decade after Japan's annexation, colonial Seoul's expansion was accepted by residents as an imminent future, corroborated by the Keijo Urban Planning Research Group's activities, although led mainly by Japanese capitalists and bureaucrats with limited Korean input. This transformation to Greater Keijo provided an opportunity to address not only the positive metropolis vision but also urban problems like poverty, insufficient utilities, and transportation. Secondly, through chronological analysis, the purpose and underlying demands supporting expansion gradually changed. Discussions until around 1930 aimed to resolve urban problems and promote growth. But after 1931's Manchurian Incident, the emphasis shifted to strengthening the war effort and enabling better functioning within the Japanese economic bloc.